Receiving a diagnosis of young onset dementia: a scoping review of lived experiences. (2nd January 2021) - O'Malley, Mary; Carter, Janet; Stamou, Vasileios; LaFontaine, Jenny; Oyebode, Jan; Parkes, Jacqueline
Abstract: Objectives: Personal experiences of receiving a diagnosis of young onset dementia (YOD) are often overlooked in a complex assessment process requiring substantial investigation. A thematic synthesis of published until November 2018 qualitative studies was completed to understand the lived experiences of younger people. This informed a Delphi study to learn how diagnostic processes could be improved, identify the strengths and weaknesses of current approaches, and help educate professionals concerning key issues. Method: Systematic searches of bibliographic databases were conducted involving self-reported experiences of diagnosis of YOD. Eight out of 47 papers identified were quality assessed using Walsh & Browne's criteria for methodological appraisal. Results: The review emphasises that delays in diagnosis can often be attributed to (1) delays in accessing help, and (2) misattribution of symptoms by the clinician. The impact of diagnosis is influenced by the clinician's use of language; and reactions to diagnosis varied from feelings of reassurance (in that their symptoms are now explained), to shock and destabilisation. Conclusion: This review suggests that improving the recognition of presenting symptoms, reducing diagnostic errors, and identifying the emotional needs arising from diagnosis are required to improve the diagnostic experience for younger adults, and to promote future engagement with services.